The Religious Guidance Efforts to Prevent Student Moral Decadence - Musnar Indra Daulay; Pandu Adi Cakranegara; Fauzi Aldina; Supeno Supeno; Achmad Syarifudin (AL-ISHLAH: Jurnal Pendidikan, 2021)
This study aims to analyze efforts to prevent moral decadence in students through religious development. The research method used is qualitative research with a phenomenological approach. The objects in this research are teachers and their activities, programs, and extracurricular activities. Informants in this study were principals, vice principals, subject teachers, and activity supervisors. Data were collected through observation and in-depth interviews. Data were analyzed by data reduction, data presentation, and concluding. This study concludes that there are three strategies carried out by the school in an effort to prevent the occurrence of adolescent moral decadence, namely teacher exemplary, religious programs, and religious extracurriculars.